ESSENCE AND ELEMENTAL COMPOSITION OF THE CORPORATE GOVERNANCE SYSTEM - Олiм, Валентин (SWorldJournal, 2022)
The article presents the results of a study of essential elements of effective corporate governance. It is noted that the essential characteristics of corporate governance is the protection, harmonization and realization of stakeholders' interests of corp